2021
DOI: 10.32996/jeltal.2021.3.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of General Self-efficacy on Academic Achievement Using Path Analysis: A Preliminary Study

Abstract: Although self-efficacy is a construct born originally out of and into the field of psychology, its importance and relevance extend de facto outside its original field of research to span multiple closely related disciplines including, but in no way limited to, applied linguistics and educational psychology mainly for its demonstrably strong association to a vast range of language-related educational phenomena. In the present study, we set out to examine, by means of the Spearman correlational test and through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
2
9
1
3
Order By: Relevance
“…Third, math proficiency predicted performance in physics, but its contribution across academic majors and modes of instruction was rather modest. In agreement with Hudson and Rottmann (1981), our findings suggest that besides math competency, other factors are likely to be more influential, such as the general confidence that students exhibit in their abilities to overcome obstacles and complete tasks given to them (i.e., general selfefficacy; Chen et al, 2001;Bouih et al, 2021). In another study involving math learning (Pilotti et al, 2022a), we found no differences in female students' general self-efficacy between STEM and non-STEM majors.…”
Section: Discussionsupporting
confidence: 71%
“…Third, math proficiency predicted performance in physics, but its contribution across academic majors and modes of instruction was rather modest. In agreement with Hudson and Rottmann (1981), our findings suggest that besides math competency, other factors are likely to be more influential, such as the general confidence that students exhibit in their abilities to overcome obstacles and complete tasks given to them (i.e., general selfefficacy; Chen et al, 2001;Bouih et al, 2021). In another study involving math learning (Pilotti et al, 2022a), we found no differences in female students' general self-efficacy between STEM and non-STEM majors.…”
Section: Discussionsupporting
confidence: 71%
“…However, albeit the findings of this study may not have concurred with researchers reporting boys' superiority (Hutt, 1979;Collis & Williams, 1987), they do not stand in opposition to an abundant mass of evidence drawn from other more published studies concerned with the same issue (Powell, 1979;Ekstrand, 1980;Burstall, 1981;Stockard & Wood, 1984;Riding & Banner, 1986). This tendency to favor girls over boys with regards to language performance has recently been well-attested and stressed by several investigations (Licht et al, 1989;Halpern, 1992;Murphy, 2010;Główka, 2014;Benattabou, 1990;Khoumich & Benattabou, 2020;Bouih et al, 2021).…”
Section: Resultscontrasting
confidence: 57%
“…They argued that some reasons for self-efficacy, such as performance accomplishments, vicarious experience, oral encouragement, and emotive provocation, should be emphasized by instructors to enhance learner academic achievement. Bouih et al (2021) found out that self-efficacious learners have remarkable achievements in academic environments. Furthermore, some studies have shown that EFL learners’ self-efficacy is significantly correlated with their language skills.…”
Section: Review Of Literaturementioning
confidence: 99%